Design of fully adaptive routing and hybrid VC allocation in wireless NOC. (February 2022) - Ouyang, Yiming; Li, Ruifeng; Hu, Chunlei; Wang, Qi; Lu, Yingchun; Liang, Huaguo
Abstract: Wireless network-on-chip (WiNoC) establishes a long-range single-hop wireless links on the base of the traditional planar metal interconnects network, which improve network performance in several aspects. The establishment of wireless link improves the diversity of path for packet transmitting, while simultaneously aggravates the deadlock problem, leading it to more complicated condemn. The traditional routing mechanism of wireless network on chip can avoid deadlock by sacrificing the adaptability of transmitting, which leads to unbalanced and insufficient use of limited on chip resources. In this paper, a fully adaptive routing mechanism is proposed to balance buffer utilization. At the same time, we proposed a hybrid virtual channel allocation strategy in order to make full use of buffer resources. For a large number of single-flit wired packets and wireless packets, more aggressive non-atomic allocation is adopted, and the remaining packets are arranged with atomic allocation to avoid potential deadlock. Experimental results showed that compared with the traditional deadlock solutions, the proposed scheme introduces less area and power consumption, and balances the utilization of buffer resources. Under the non-uniform Traffic Patterns, the proposed scheme has better performance in terms of delay and throughput, achieves 62.0% improvement compared to the traditional counterpart.